Artemisia princeps as a Potential Natural Iron Source: A Systematic Review of Pharmacological Evidence and Iron Bioavailability Gaps - Jeri Nobia Purnama; Teguh Akbar Budiana; Erick Khristian; Ruhyandi Ruhyandi (Molecular and Cellular Biomedical Sciences, 2026)
Artemisia princeps is widely used in traditional Asian medicine and is well known for its diverse pharmacological properties. Scientific evidence supporting its role as a natural source of iron remains limited. Several medicinal plants have been reported to contain measurable iron and to improve iron status. This systematic review aimed to examine the pharmacological activities of A. princeps critically and to contextualize the limited iron-related evidence for this plant, compared with other medicinal plants with established iron content or bioavailability. A systematic literature search was conducted in PubMed and ScienceDirect up to April 2025, following PRISMA guidelines and the PICOC framework. The extracted data were organized into two categories: (1) pharmacological activities of A. princeps, and (2) iron content and bioavailability-related outcomes of other medicinal plants. Eight studies investigating A. princeps were identified, predominantly reporting anti-inflammatory, antioxidant, and metabolic effects. Only one study reported the iron content of A. princeps, without evaluating iron bioavailability or haematological outcomes. In contrast, nine studies on plants such as Astragalus membranaceus, Beta vulgaris, and Moringa oleifera demonstrated improvements in haemoglobin levels and other iron-related parameters in animal models and, in some cases, human studies. Current evidence indicates that while A. Princeps possesses broad pharmacological activity; its potential as a source of bioavailable iron has not been adequately investigated. This review highlights substantial evidence gaps and underscores the need for targeted studies assessing the iron content, bioavailability, and haematological effects of A. princeps, rather than overstating its current role in iron-deficiency management. Keywords: A. princeps, iron deficiency anemia, biological products, plants, natural products